Time Utilization by Hospital Attendants and Housekeeping Staffs in a Tertiary Level Hospital - Harikrishna GL; Haseena TA (International Journal of Community Health Nursing And Practices, 2023)
Introduction: Time management refers to the deliberate and conscious management of one's time to effectively allocate it to specific activities, with the aim of enhancing productivity and efficiency. Efficient time utilization can lead to improved employee productivity, streamlined job performance, and effective task completion. Additionally, it enables employees to accomplish necessary tasks and assists organizations in achieving their goals by effectively recording and guiding their activities. The objectives of this study were to assess how hospital attendants and housekeeping staff members in a tertiary care hospital utilize their time. Methods: The study employed a descriptive research design to carry out the investigation. 20 observations of hospital attendants and housekeeping staffs were made by the investigators. An observation checklist was prepared and utilized by the researcher to assess the time utilization by hospital attendants and housekeeping staffs. The data were analyzed by descriptive statistics. Results: The mean time taken by hospital attendants for sweeping and mopping is 184 minutes and helping in patient care is 68 minutes. Total time spend for working is 587 minutes as compared to 720 minutes as standard. The mean time spent by housekeeping staff in toilet and bathroom cleaning is 132 minutes and leisure time is 92 minutes. Conclusion: Education is an essential part of care and an effective method for improving the knowledge about the importance of time management and helps in improving the quality of patient care. The findings of the study could be utilized in clinical areas in improving the effective evidence-based care to patients.
Keywords: Time utilization; hospital attendants; housekeeping staffs